Transfer Pricing Methods An Applications Guide - ROBERT FEINSCHREIBER (John Wiley & Sons, Inc., 2004)
Transfer pricing, for tax purposes, is the pricing of intercompany transactions that take place between affiliated businesses. The transfer pricing process determines the amount of income that each party earns from that transaction. Taxpayers and the taxing authorities focus exclusively on related-party transactions, which are termed controlled transactions, and have no direct impact on independent-party transactions, which are termed uncontrolled transactions. Transactions, in this context, are determined broadly, and include sales, licensing, leasing, services, and interest. The concept of an international corporate headquarters of a multinational corporation that uses transfer pricing to minimize worldwide taxation is no longer viable. Two impediments limit the use of transfer pricing to achieve tax minimization: (1) the tax authorities are intent on their own revenue maximization by thwarting the taxpayer’s tax minimization plans, and (2) nontax considerations may be more significant in taxation than taxation.